Sweet Potato Peel Pectin's Potential as a Suspending Agent in Pharmaceutical Formulations: The Effect of Extraction Technique - Frederick William Akuffo Owusu; Prince George jnr Acquah; Mariam El Boakye-Gyasi; Raphael Johnson; Marcel Tunkumgnen Bayor; Desmond Asamoah Bruce Otu; Samuel Nartey; Pearl Osei Akoto (Journal of Pharmacy)
Introduction: Sweet potato (Ipomoea batatas L. Lam) represents an essential underutilised crop globally. The ubiquitous hydrocolloid, pectin, with versatile pharmaceutical and cosmetic applications has been reported to be abundant in the peels. This study thus examined the impact of acid (citric acid) and alkaline (sodium hydroxide) extraction procedures on the suitability of pectin extracted from sweet potato peels as a biocompatible and economical alternative pharmaceutical suspending agent. Methods: Conventional acid and alkaline extraction procedures were utilised in sweet potato pectin extraction followed by characterisation and phytochemical evaluation. The proximate composition, FTIR spectra, secondary metabolites and degree of esterification were determined. Additionally, different concentrations (1% and 2%) of the pectins were utilised in formulating paracetamol suspensions using acacia gum as the reference and assessed for pharmaceutical quality. Results: Secondary metabolites were present in all pectins while the yield was 9.04±0.07 and 7.24±0.25 respectively for the acid and alkaline extraction methods. Quality and high methoxyl pectins with significant differences (p<0.05) in all characterisation parameters (Equivalent weight=1666.67 and 1250mg/mol; methoxyl content=16.43 and 9.57% respectively) except for ash content (3.12 and 2.95 % respectively) were obtained. FTIR highlighted characteristic functional groups in pectin. Both pectin suspensions demonstrated good however, variable significant differences (p<0.05) in flow rates, re-dispersibility, sedimentation rates, and volumes compared to acacia gum.  The pH remained mildly acidic (<7) with no physical instabilities. Conclusion: The alkaline pectin exhibited a better-suspending property than the acid pectin extract. Nevertheless, they both can be utilised as an alternative to acacia gum as a suspending agent.